Investigating and Measuring the Satisfaction of Cooperators from The Electronic Registration Services of Ardebil’s Companies (International Journal of Applied Research in Management and Economics, 2018)
The satisfaction of citizens and clients increases public trust and loyalty, national consensus, public participation and national authority, which in the current world are considered as the main indicators of efficiency measurement and development of the administrative and political system. In Iran, the main duty of cooperatives is to provide appropriate services to members to provide inputs of production and after-sales services and marketing. In this regard, commercial activities prior to production and production time and after that should be placed in the context of this type of cooperatives. With all the benefits of the use of information technology in economic and business interactions in the present era, business interactions between cooperatives are less done electronically due to the lower level of technical knowledge of the human resources of its managers, and the members of the cooperatives are weak in discussing the use of information technology techniques and cooperatives have not benefited from ICT technology in doing current affairs. There is also an unhealthy distribution network between producers and consumers that use this messed mechanism. Therefore, network coordination and management of the value of cooperatives can provide the appropriate mechanism for the electronic business model and increase the satisfaction of cooperators from the existing system. Hence, this research seeks to answer the question of how much is cooperators’ satisfaction from electronic registration services?